Information is Power : Experimental Evidence on the Long-Run Impact of Community Based Monitoring - Bjorkman Nyqvist, Martina (World Bank Group, Washington, DC, 2014)
This paper presents the results of two field experiments on local accountability in primary health care in Uganda. Efforts to stimulate beneficiary control, coupled with the provision of report cards on staff performance, resulted in significant improvements in health care delivery and health outcomes in both the short and the longer run. Efforts to stimulate beneficiary control without providing information on performance had no impact on quality of care or health outcomes. The paper shows that informed users are more likely to identify and challenge (mis)behavior by providers and as a result turn their focus to issues that they can manage locally.